Self nano emulsifying drug delivery system (SNEDDS): development, optimization and characterization of pioglitazone hydrochloride. - GIRISH CHANDRA SONI,; S.K PRAJAPATI, (International Journal of Pharma and Bio Sciences, 2017)
The objective of present study is to develop self nano emulsifying drug delivery system for lipophillic drug, pioglitazone hydrocholoride (used to treat Type 2 diabetes). Capmul PG, kolliphour EL and propylene glycol were chosen as oil, surfactant and co-surfactant respectively as they show higher solubility for pioglytazone hydrochloride. Screening of surfactant, co-surfactant is done by percent transmittance and observed for turbidity or phase separation visually. To determine stable emulsifying region, pseudo ternary phase diagram was constructed. Optimization of formulation was performed by Box Bhenken design, chosen for further study. Characterization was done for optimized formulation. Percent drug content was found to be 90.2. Emulsifying study showed transparent appearance after 24 hr, dilutability test gave percentage transmittance was found to be 99.9. In-vitro dissolution studies were conducted in stimulated gastric fluid (S.G.F) pH 1.2 showed 95.94 percent drug release while pure drug exhibited only 58.67 % within 30 minute. cloud point determine to be 53.02, particle size found 111.4 nm which is under nano size range, performing poly dispersity index (PDI) 0.22, zeta potential found to be -15.3mv, by using particle size analyzer.TEM study shows uniform spherical nano emulsion droplets provide large surface area for drug absorption. Robustness to dilution determine by using thermodynamic study and centrifugation study shows homogenous and no phase separation. From the present study it is clear that SNEDDS can be formulated to improve the dissolution and oral bioavailability of poorly water soluble drug pioglitazone hydrochloride.